Macroeconomic stabilisation properties of a euro area unemployment insurance scheme - Christoph Kaufmann; Maria Grazia Attinasi; Sebastian Hauptmeier (European Central Bank (ECB), 2020)
In this paper we use a medium-scale DSGE model to quantitatively assess the macroeconomic stabilisation properties of a supranational unemployment insurance scheme. The model is calibrated to the euro area's core and periphery and features a rich fiscal sector, sovereign risk premia and labour market frictions. Adopting both simple policy rules and optimal policies, our simulations point to enhanced business cycle synchronisation and interregional consumption smoothing. Depending on the exact specification, the results suggest a reduction in the volatility of consumption by up to 49% at the region-level, while the cross-regional correlation of unemployment and in ation increases by up to 52% and 27%, respectively, compared to the decentralised setting. The higher degree of inter-regional risksharing comes at the cost of sizable fiscal transfers. Limiting such transfers via claw-back mechanisms implies a much weaker degree of stabilisation across countries.
Keywords: F45; E63; E62; E24; 330; Monetary union; Fiscal union; Unemployment insurance; Optimal policy